Urbanization leads to asynchronous homogenization of soil microbial communities across biomes - Bangxiao Zheng; Nan Hui; Ari Jumpponen; Changyi Lu; Richard Pouyat; Katalin Szlavecz; David A. Wardle; Ian Yesilonis; Heikki Setälä; D. Johan Kotze (Environmental Science and Ecotechnology, 2025)
Soil bacterial and fungal communities play fundamental roles in biogeochemical cycles and ecosystem stability. Urbanization alters soil properties and microbial habitats, driving shifts in community composition, yet the divergent responses of bacteria and fungi and their ecological consequences remain inadequately understood. To elucidate these differential responses, we investigated soil bacterial and fungal communities along an urbanization gradient, ranging from undisturbed reference forests to urban parks, across three distinct climatic regions. To capture different disturbance intensities, urban parks were classified by tree age into old parks (>60-year-old trees) and young parks (10–20-year-old trees). Climate had a strong influence on soil microbiota, yet urbanization still significantly altered both bacterial and fungal communities in all regions. Urban disturbances homogenized soil microbial communities: average similarity among bacterial communities increased from ∼79% in forests to ∼85% in young urban parks, indicating substantial homogenization, whereas fungal communities showed little homogenization. Urbanization also homogenized microbial functional traits, with a greater reduction in trait dissimilarity for bacteria than for fungi. Bacterial communities exhibited high adjustability to urban conditions, dominated by generalist taxa (∼90%), whereas fungal communities consisted mostly of specialists (∼83%). Despite these asynchronous responses—bacteria adjusting and homogenizing more than fungi—overlapping functional traits between bacteria and fungi help maintain functional resilience in urban ecosystems.